Brain Endothelial miR-146a Negatively Modulates T-Cell Adhesion through Repressing Multiple Targets to Inhibit NF-κB Activation. Issue 3 (March 2015) - Wu, Dongsheng; Cerutti, Camilla; Lopez-Ramirez, Miguel A; Pryce, Gareth; King-Robson, Josh; Simpson, Julie E; van der Pol, Susanne MA; Hirst, Mark C; de Vries, Helga E; Sharrack, Basil; Baker, David; Male, David K; et al.
Pro-inflammatory cytokine-induced activation of nuclear factor, NF-κB has an important role in leukocyte adhesion to, and subsequent migration across, brain endothelial cells (BECs), which is crucial for the development of neuroinflammatory disorders such as multiple sclerosis (MS). In contrast, microRNA-146a (miR-146a) has emerged as an anti-inflammatory molecule by inhibiting NF-κB activity in various cell types, but its effect in BECs during neuroinflammation remains to be evaluated. Here, we show that miR-146a was upregulated in microvessels of MS-active lesions and the spinal cord of mice with experimental autoimmune encephalomyelitis. In vitro, TNFα and IFNγ treatment of human cerebral microvascular endothelial cells (hCMEC/D3) led to upregulation of miR-146a. Brain endothelial overexpression of miR-146a diminished, whereas knockdown of miR-146a augmented cytokine-stimulated adhesion of T cells to hCMEC/D3 cells, nuclear translocation of NF-κB, and expression of adhesion molecules in hCMEC/D3 cells. Furthermore, brain endothelial miR-146a modulates NF-κB activity upon cytokine activation through targeting two novel signaling transducers, RhoA and nuclear factor of activated T cells 5, as well as molecules previously identified, IL-1 receptor-associated kinase 1, and TNF receptor-associated factor 6. We propose brain endothelial miR-146a as an endogenous NF-κB inhibitor in BECs associated with decreased leukocyte adhesion during neuroinflammation.